The Effect of Kegel Exercises on the Healing of Perineal Wounds in Normal Postpartum Mothers at Morowali District Hospital - Yuliadia, Kartika; Kartini, Farida; Rokhanawati, Dewi; Ari Astuti, Dhesi (Universitas STRADA Indonesia, 2025)
During pregnancy and childbirth, women undergo significant physiological changes, including the loosening of the abdominal wall, vaginal canal, and pelvic floor muscles. Approximately 90% of women experience perineal tears during delivery, regardless of whether an episiotomy is performed. One approach to strengthening the pelvic floor muscles postpartum is through Kegel exercises. A quasi-experimental study design with quantitative random sampling was employed to compare the REEDA scale scores of the intervention group and the control group. The data were analyzed using the Mann-Whitney U test. The findings revealed that the intervention group, which performed Kegel exercises, had significantly lower REEDA scores than the control group, indicating faster recovery of perineal lesions in postpartum mothers at Morowali Regional Hospital in 2024 (p = 0.001, Sig. (2-tailed) < 0.05). It is recommended that postpartum mothers regularly engage in Kegel exercises to promote the healing of perineal tears.